Evaluating Implementation of the Transparency and Openness Promotion Guidelines: Reliability of Instruments to Assess Journal Policies, Procedures, and Practices - Kianersi S. (2023)
The Transparency and Openness Promotion (TOP) Guidelines describe modular standards that journals can adopt to promote open science. The TOP Factor quantifies the extent to which journals adopt TOP in their policies, but there is no validated instrument to assess TOP implementation. Moreover, raters might assess the same policies differently. Instruments with objective questions are needed to assess TOP implementation reliably. In this study, we examined the interrater reliability and agreement of three new instruments for assessing TOP implementation in journal policies (instructions to authors), procedures (manuscript-submission systems), and practices (journal articles). Independent raters used these instruments to assess 339 journals from the behavioral, social, and health sciences. We calculated interrater agreement (IRA) and interrater reliability (IRR) for each of 10 TOP standards and for each question in our instruments (13 policy questions, 26 procedure questions, 14 practice questions). IRA was high for each standard in TOP; however, IRA might have been high by chance because most standards were not implemented by most journals. No standard had “excellent” IRR. Three standards had “good,” one had “moderate,” and six had “poor” IRR. Likewise, IRA was high for most instrument questions, and IRR was moderate or worse for 62%, 54%, and 43% of policy, procedure, and practice questions, respectively. Although results might be explained by limitations in our process, instruments, and team, we are unaware of better methods for assessing TOP implementation. Clarifying distinctions among different levels of implementation for each TOP standard might improve its implementation and assessment (study protocol: https://doi.org/10.1186/s41073-021-00112-8).